Relationship of Spiritual Aspects with Hyperemesis Gravidarum Incidence of Pregnant Women in Tinambung District in 2020 - Sanusi, Husnul Khatimah; Darmawansyih, Darmawansyih; Nadyah, Nadyah; Sari, Jelita Inayah (Green Medical Journal, 2021)
Introduction: Nausea and vomiting is a common thing and physiological in early pregnancy. This condition can be severe if continued and causes a pregnancy disorder called hyperemesis gravidarum. Mothers with hyperemesis gravidarum based on data at the Tinambung Health Center in 2018 amounted to 47 people and in 2019 there were 58 people. The risk factor for hyperemesis gravidarum is associated with several factors, one of which is the spiritual aspect of the mother. Methods: This type of research is an analytic survey using cross-sectional. Sampling from 344 populations with a purposive technique for 78 samples. Data analysis using Chi-Square test on SPSS program. Results: The Majority of respondents had moderate and low spiritual aspects, namely 33 respondents (42.3%). The chi square test showed p-value = 0.042 (<0.05) so that the spiritual aspect significantly affected the status of hyperemesis gravidarum. Conclusion: This study concludes that there is a significant relationship between the spiritual aspects of the mother with the occurrence of hyperemesis gravidarum in Tinambung District.